Trabajo de parto humanizado, importancia del acompañamiento para prevenir la violencia obstétrica en el Hospital Nicolás Cotto Infante de Vinces, Los Ríos, enero – junio 2019. - Figueroa León, Alexandra Michel (2020)
The importance of accompaniment during labor to avoid obstetric violence is based on the support provided by the person of trust of the pregnant woman, thus the companion by observing the work of the health team will prevent any type of obstetric violence. It should be emphasized that, according to previous studies, the support provided by the companion is not only physical, but also emotional, informative and representative; Thus, during labor, pregnant women will experience less pain when feeling safe at all times. In this way we will know what is the importance of the accompaniment in humanized childbirth at the Nicolás Cotto Infante de Vinces Hospital. Objective: to determine the importance of accompaniment in humanized labor as prevention of obstetric violence. Under the thesis that patients suffer from obstetric violence at the Nicolás Coto Infante Hospital, a series of questions are raised that allow addressing the importance of accompaniment during labor. International studies are raised where it is an obligation to be accompanied in the delivery room otherwise complaints will be imposed for large sums of money. And within the national scope it is a right of the pregnant woman in this way, obstetric violence itself will be avoided and it is prevented that during any complication that exists in labor, it is not indicated as “medical negligence”. Methodology: applied, descriptive, cross-sectional, retrospective, non-experimental study, a total of postpartum patients who are hospitalized in the maternity ward of the Nicolás Coto Infante Hospital have been selected, including a total of 73 postpartum women in the study. Results: Through a survey of a sample of 73 women hospitalized in the maternity area of the Nicolás Cotto Infante Hospital, to establish the causes that influence a group of women on the importance of accompaniment in humanized labor to prevent Obstetric violence, it can be deduced that the factor that has more incidence.